GaPt Supported Catalytically Active Liquid Metal Solution Catalysis for Propane Dehydrogenation-Support Influence and Coking Studies - Raman, Narayanan; Wolf, Moritz; Heller, Martina; Heene-Würl, Nina; Taccardi, Nicola; Haumann, Marco; Felfer, Peter; Wasserscheid, Peter (ACS Catalysis, 2021)
Supported catalytically active liquid metal solutions (SCALMS) of Pt in Ga (2 at.-% Pt) were studied in the temperature range of 500 to 600 °C for propane dehydrogenation. A facile synthesis procedure using ultrasonication was implemented and compared to a previously reported organo-chemical route for gallium deposition. The procedure was applied to synthesize GaPt-SCALMS catalyst on silica (SiO2), alumina (Al2O3), and silicon carbide (SiC) to investigate the effect of the support material on the catalytic performance. The SiC-based SCALMS catalyst showed the highest activity, while SiO2-based SCALMS showed the highest stability and lowest cracking tendency at higher temperatures. The selectivity toward propene for the SiO2-based catalyst remained above 93% at 600 °C. The catalysts were analyzed for coke content after use by temperature-programmed oxidation (TPO) and Raman spectroscopy. While the SiC- and SiO2-supported SCALMS systems showed hardly any coke formation, the Al2O3-supported systems suffered from pronounced coking. SEM-EDX analyses of the catalysts before and after reaction indicated that no perceivable morphological changes occur during reaction. The SCALMS catalysts under investigation are compared with supported Pt and supported GaPt solid-phase catalyst, and possible deactivation pathways are discussed.
CRIS-Team Scopus Importer:2021-11-19
Keywords: coking; dehydrogenation; gallium; platinum; SCALMS; supported liquid catalysis